MENJADI GURU SEKOLAH DASAR YANG INOVATIF DI ERA REVOLUSI INDUSTRI 4.0 - Teguh Teguh (Universitas Sriwijaya, 2020)
AbstractIn the era of an industrial revolution of 4.0 education integrated Cyber technology into learning to prepare students for digital challenges. Students need to have the competence to be able to utilize information and communication technology. A diverse range of students with varying degrees of digital divide also demand teachers to be creative and innovative in their learning. Innovative learning by resting on the four principles of learning is student-centered, collaborative, context-and school-integrated with the community. Keywords: Innovative elementary school teacher, Industrial Revolution 4.0 AbstrakPada era revolusi industri 4.0 pendidikan mengintegrasikan teknologi siber ke dalam pembelajaran demi mempersiapkan siswa untuk menghadapi tantangan digital. Siswa perlu memiliki kompetensi untuk dapat memanfaatkan teknologi informasi dan komunikasi. Beragam kemampuan siswa dengan tingkat kesenjangan digital yang beragam pula menuntut guru untuk kreatif dan inovatif dalam pembelajaran. Pembelajaran yang inovatif dengan bertumpu pada empat prinsip pembelajaran yaitu berpusat pada siswa, bersifat kolaborasi, memiliki konteks, dan sekolah terintegrasi dengan masyarakat. Kata kunci: Guru SD Inovatif, Revolusi Industri 4.0